TALEMPONG AGUANG: REPRESENTATION OF AESTHETIC SYMBOLS AND POWER IN THE BATAGAK PANGULU CEREMONY AT SARIAK VILLAGE AGAM DISTRICT - Wahyuni, Annita; Indra Sastra , Andar (PT. Antis International Publisher, 2024)
Objective: This study aims to examine the role of Talempong Aguang in the Batagak Pangulu Ceremony in Nagari Sariak, Agam Regency, focusing on its function as an aesthetic symbol and its representation of power within the social structure of the community. Method: A qualitative approach was employed, utilizing field research to gather data. Primary data sources involved three main groups: Penghulu (Niniek Mamak), Talempong players, and the community. Results: The findings reveal that Talempong Aguang serves as an aesthetic symbol representing harmony, beauty, and societal prosperity in the Batagak Pangulu ceremony. Additionally, it functions as a symbol of power, reflecting authority and hierarchical positions in the community's social structure. The instrument also significantly influences the community’s understanding of social and cultural structures, reinforcing awareness of social hierarchies and cultural values embedded within traditional ceremonies. Novelty: This study highlights the dual role of Talempong Aguang as both an aesthetic and power symbol, emphasizing its critical impact on shaping social and cultural awareness in Nagari Sariak’s traditional ceremonies.